Jender dalam Kisah-kisah al-Qur’an - Jalil, Abdul (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2011)
It considers equality issues between men and women’s rights in some of the advanced societies of the most important issues of critical importance to the achievement of social justice among individuals, and here appeared aware of gender or gender convention to discuss those issues. Muslims as a community religious and social limitations and organized his own and different from country to country, but they inevitably come back in a lot of things and issues to the Koran as a book in which the divine guidance and the interests of all individuals. This research related to women’s and men’s rights issues and the relationship between them from the Koran perspective, where the Koran is a difference between use of words and words by context, use of the word male and female in the context of creation and differentiation diversity in human formation, while the use of the word of men and women when he was the context of the social and cultural role, Quran stories and also different style for the Torah, where it enters the principles and values and social sermons through his narrative and his words and talks in story mode